2013
DOI: 10.1016/j.gexplo.2013.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Application of neural network model for the prediction of chromium concentration in phytoremediated contaminated soils

Abstract: The assessment of chromium concentrations in plants requires the quantification of a large number of soil factors that affect their potential availability and subsequent toxicity and a mathematical model that predicts their relative concentrations. Many soil characteristics can change the availability of chromium (Cr) to plants in soils. However, accurate, rapid and simple predictive models of metal concentrations are still lacking in soil and plant analysis. In the present work a novel artificial neural netwo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…ANN is a type of computational simulation based on mathematical models which works on the basis of the neurological functions of the brain (Manahan, 2010). The Application of ANN involves mathematical modelling that can be used for the purpose of quantification of Cr concentration with the dwarf bean and the amount of phytoremediation being performed by the plant (Hattab et al, 2013). The mechanism of gene editing involves the process of manipulation of DNA with the help of engineered nucleases.…”
Section: Artificial Neural Network (Ann) Mediated Bioremediationmentioning
confidence: 99%
“…ANN is a type of computational simulation based on mathematical models which works on the basis of the neurological functions of the brain (Manahan, 2010). The Application of ANN involves mathematical modelling that can be used for the purpose of quantification of Cr concentration with the dwarf bean and the amount of phytoremediation being performed by the plant (Hattab et al, 2013). The mechanism of gene editing involves the process of manipulation of DNA with the help of engineered nucleases.…”
Section: Artificial Neural Network (Ann) Mediated Bioremediationmentioning
confidence: 99%
“…A critical aspect of predicting soil pollution is the determination of the concentrations of inorganic and organic pollutants. Since examining the relationship between different soil properties and pollutant concentrations is complex, time-consuming, and expensive, in recent years, emphasis has been placed on developing models that simulate these relationships [ 1 , 2 ]. The main objective of this study is to determine the possibilities of predicting the impact of land use and soil type on the concentrations of heavy metals (HMs) and phthalates (PAEs) using an artificial neural network (ANN) model.…”
Section: Introductionmentioning
confidence: 99%
“…In the environmental forecasting context, recent experiments have reported that ANNs may offer a promising alternative for estimating heavy metals' concentration (25)(26)(27)(28)(29)(30) According to the knowledge of the authors of this study, there is not any published work in the literature related to comparison of two different neural networks (MLP and RBF), in forecasting of heavy metals concentration in groundwater resources of Toyserkan plain.…”
Section: Introductionmentioning
confidence: 99%